PERSONAL DEIXIS USED IN MALCOLM X’S “THE BALLOT OR THE BULLET” SPEECH - Gobel, Fakhirah; Lihawa, Kartin; Hasanuddin, Hasanuddin (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
This study aims to observe and describe the types of personal deixis used in Malcolm X’s “The Ballot or The Bullet” speech using the theory of Yule (1996). In collecting the data, this qualitative descriptive method was used by watching the video documentation, downloading the transcript, and reading the script that contain personal deixis in the speech. The theory of Miles and Huberman (1994) was used in this study as the steps to analyze the data which consists of data reduction, data display, and data drawing. The result of this study found out there was 662 deixis that consisted of three types of person deixis which are first-person, second-person, and third-person divided into 14 types of personal deixis use, i.e 222 first-person deixes, 211 second-person deixis, and 229 third-person with second-person deixis You (174 times use), They (84 times use) and We (79 times use) as the most often used type in the speech. In addition, Malcolm X used personal deictic expressions as a way to motivate and influence the African-American community in empowering the important philosophy of black nationalism against the racism issue of the African-American community in the 20th-century era.